High-Resolution Metabolomics for Nutrition and Health Assessment of Armed Forces Personnel. (August 2016) - Accardi, Carolyn Jonas; Walker, Douglas I.; Uppal, Karan; Quyyumi, Arshed A.; Rohrbeck, Patricia; Pennell, Kurt D.; Mallon, COL Timothy M.; Jones, Dean P.
Abstract : Objective: The aim of this study was to test the utility of high-resolution metabolomics (HRM) for analysis of nutritional status and health indicators in military personnel. Methods: Serum samples from 400 military personnel were obtained from the Department of Defense Serum Repository (DoDSR) and analyzed for metabolites related to nutrition and health status. Metabolic profile organization was studied using modulated modularity clustering (MMC). Results: HRM provided quantitative measures of 61 metabolites across chemical classes for use as nutritional and clinical biomarkers. Levels were comparable to reported values except for arginine and glutamine, which were above and below reference ranges, respectively. MMC generated five clusters, three of which were associated and contained amino acids. The others contained lipids and mitochondria-related metabolites. Conclusions: HRM analysis of serum is suitable for real-time and/or retrospective evaluation of nutrition and health status of specific military cohorts. Abstract : Supplemental Digital Content is available in the text